Lesions of the posterior limb of the internal capsule in neuromyelitis optica spectrum disorder. (4th May 2017) - Long, Youming; Wu, Linzhan; Zhong, Rong; Ouyang, Xiaoming; Liang, Junyan; Gao, Cong; Chen, Xiaohui; Qiu, Wei; Chang, Yanyu; Wang, Zhanhang; Ye, Jinlong
Abstract: Posterior limb of the internal capsule lesions (PLICL) are one of the MRI features of neuromyelitis optica spectrum disorder (NMOSD). However, there is no evidence that such lesions are pathogenically related to NMOSD. We retrospectively analyzed features of PLICL in NMOSD, and other central nervous system inflammatory disorders, in 561 patients. We also examined the pathological samples of six patients. Of the 561 patients investigated, PLICL were found in 65 patients (11.6%). Lesions were bilateral in 26 cases (40%) and unilateral in 39 cases (60%). Unilateral lesions were mainly located on the left side (74.3%, 29/39). Of the 65 patients with PLICL, 46 patients had NMOSD (70.8%) and were positive for anti-aquaporin (AQP4-IgG), four had NMOSD (6.2%) and were AQP4-IgG negative, 10 patients had multiple sclerosis (MS), three patients had NMDAR encephalitis, and two had autoimmune meningoencephalitis. Of the six patients whose pathological samples were evaluated, all had PLICL and were negative for AQP4-IgG, and none had pathological NMOSD lesion features. These cases included three patients with multiple sclerosis, one with anti-N-methyl-D-aspartate receptor encephalitis, and two with autoimmune meningoencephalitis. In conclusion, PLICL are found not only in patients with NMOSD, but also in MS and other disorders.